2021
DOI: 10.2147/jhc.s332420
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib Combined with Anti-PD-1 Antibodies Plus Transcatheter Arterial Chemoembolization for Unresectable Hepatocellular Carcinoma: A Multicenter Retrospective Study

Abstract: Background: Lenvatinib (LEN) combined with anti-PD-1 antibodies (PD-1) exerted promising effects on unresectable hepatocellular carcinoma (uHCC). We assessed the safety and clinical efficacy of triple therapy [LEN+PD-1+transcatheter arterial chemoembolization (TACE)] in uHCC. Methods: uHCC patients with an ECOG PS score of 0-1 and Child-Pugh class A who underwent triple therapy were included. The primary endpoint was objective response rate (ORR) based on mRECIST. Secondary endpoints were conversion rate to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 37 publications
8
115
0
Order By: Relevance
“…In the current study, treatment-related AEs occurred in 85% of patients. The incidence of AEs was in accordance with the other triple therapy cohort (29), which reported AEs of 74.2%. AEs of higher grade (grade ≥3) were 14.5% in their cohort and 28% in our cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, treatment-related AEs occurred in 85% of patients. The incidence of AEs was in accordance with the other triple therapy cohort (29), which reported AEs of 74.2%. AEs of higher grade (grade ≥3) were 14.5% in their cohort and 28% in our cohort.…”
Section: Discussionsupporting
confidence: 88%
“…At the third month, the ORR and DCR were 72.6% and 95.5%, respectively, and the median PFS was 11.4 months. In another cohort of 62 patients treated with TACE plus lenvatinib and anti-PD-1 therapy ( 29 ), they reported an ORR of 80.6%, and 32 (53.2%) patients successfully converted to resectable HCC; among these patients, 29 patients underwent resection, and 16 patients achieved a pathological complete response. Although comparisons between different studies should be cautious, these data indicated an encouraging efficacy of this triple therapy for uHCC.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 97 were excluded by duplicating, 1,353 by screening titles and abstracts, and another 22 more by reading the full text. Finally, 15 records were assessed to be eligible for this meta-analysis ( 21 , 25 , 30 42 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies came from China, and all the studies were retrospective, three of which were multi-centered ( 25 , 30 , 34 ). The baseline characteristics in each study were depicted in Table 1 , as well as the results of quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, immunotherapy, especially immune-checkpoint inhibitor therapies, has been successful in treating advanced HCC (33,34). Combining locoregional therapy approaches such as TACE with immunotherapy is an interesting treatment plan, which may provide better results (35). The BIS model can divide patients into high and low recurrence risk groups, which can be used to filter patients for receiving adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%